1998
DOI: 10.1002/(sici)1097-0142(19980401)82:7<1310::aid-cncr14>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Breast carcinoma survival analysis for african american and white women in an equal-access health care system

Abstract: In our study, the 5-year risk of death, from any cause, was 1.37 for African American women with breast carcinoma; in other words, the mortality rate for African AmeriThe authors are grateful to Ruth Byers, Staff can women was 24.77% compared with 18.08% for white women. In the latest Officer, U.S. Army Medical Command, for providing many reports and substantial guidance SEER data, the 5-year relative risk of death for African American women compared in the use and management of the Department with white women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(86 citation statements)
references
References 31 publications
(34 reference statements)
4
80
0
1
Order By: Relevance
“…[23][24][25][26][27][28][29] However, the results of the current study support results of a study by Wojcik et al 30 who reported that survival remains significantly worse for African-American women even with equivalent treatment. In the Wojcik et al study, survival was significantly better for patients who received BCS with radiation therapy than for those who received BCS alone.…”
Section: Discussionsupporting
confidence: 85%
“…[23][24][25][26][27][28][29] However, the results of the current study support results of a study by Wojcik et al 30 who reported that survival remains significantly worse for African-American women even with equivalent treatment. In the Wojcik et al study, survival was significantly better for patients who received BCS with radiation therapy than for those who received BCS alone.…”
Section: Discussionsupporting
confidence: 85%
“…[2][3][4][5][6][7][8] Possible explanations advanced for this disparity in breast cancer mortality include lack of access to health insurance and medical care, 25 differences in treatment, 26,27 or socioeconomic factors. 7,28,29 Other investigations have shown that equal access to medical care does not eliminate completely the survival disadvantage for African American women, [30][31][32][33] and race alone has been suggested as an independent predictor for survival. [34][35][36] African American women were noted to have significantly earlier age at diagnosis, high grade tumors, and a higher proportion of ERnegative and PR-negative cancers, 3,6,[37][38][39][40][41][42] suggesting that breast cancer is biologically different in African American women.…”
Section: Discussionmentioning
confidence: 93%
“…Wojcik et al 25 reported survival differences between African-American and Caucasian women who had equal and free access to healthcare services through the Department of Defense (DoD). Their findings suggested that for African-American women the risk of breast carcinoma mortality relative to the race-specific national average was reduced.…”
Section: Resultsmentioning
confidence: 99%